Production of neutral pions and eta-mesons in pp collisions measured with ALICE - Reygers, Klaus (Journal of physics. G, Nuclear and particle physics, 2011)
Invariant cross sections for neutral pions and η mesons in pp collisions at , 2.76 and 7 TeV were measured by the ALICE detector at the LHC. Next-to-leading order perturbative QCD calculations describe the π0 and η spectra at 0.9 TeV, but overestimate the measured cross sections at 2.76 and 7 TeV. The measured η/π0 ratio is consistent with mT scaling at 2.76 TeV. At 7 TeV, indications for a violation of mT scaling were found.
Gesehen am 15.09.2022